Professor Jerzy Sadowski 1924–2014 - Barbara SZUDROWICZ (Archives of Acoustics)
Professor Jerzy Sadowski – outstanding Polish scientist, a specialist in acoustics – construction, industrial, architectural and environmental – passed away on 28th July 2014.